Design of a radiation tolerant system for total ionizing dose monitoring using floating gate and RadFET dosimeters. (4th April 2017) - Ferraro, R.; Danzeca, S.; Brucoli, M.; Masi, A.; Brugger, M.; Dilillo, L.
Abstract: The need for upgrading the Total Ionizing Dose (TID) measurement resolution of the current version of the Radiation Monitoring system for the LHC complex has driven the research of new TID sensors. The sensors being developed nowadays can be defined as Systems On Chip (SOC) with both analog and digital circuitries embedded in the same silicon. A radiation tolerant TID Monitoring System (TIDMon) has been designed to allow the placement of the entire dosimeter readout electronics in very harsh environments such as calibration rooms and even in the mixed radiation field such as the one of the LHC complex. The objective of the TIDMon is to measure the effect of the TID on the new prototype of Floating Gate Dosimeter (FGDOS) without using long cables and with a reliable measurement system. This work introduces the architecture of the TIDMon, the radiation tolerance techniques applied on the controlling electronics as well as the design choices adopted for the system. Finally, results of several tests of TIDMon under different radiation environments such as gamma rays or mixed radiation field at CHARM are presented.